The influence of performance feedback and top management team orientation on decisions about R&D in technology-based firms. (May 2022) - Saemundsson, Rögnvaldur; Candi, Marina; Sigurjonsson, Throstur Olaf
Abstract: The purpose of this work is to investigate the influence of performance feedback on decisions about R&D—more specifically R&D intensity and R&D direction, ranging from exploitation to exploration—and how this varies depending on top management team orientation. Using panel data collected from a large sample of technology-based firms over nine years, hypotheses about how the relationship between performance feedback and decisions about R&D are moderated by the technology orientation of top management teams are tested. Overall, the findings support the basic premises put forth, namely that top management team orientation influences decisions about R&D in response to performance feedback. This sheds new light on our understanding of the relationship between performance feedback and decisions about R&D in technology-based firms. Highlights: The influence of performance feedback on decisions about R&D is examined in a large longitudinal panel data set. The degree to which top management teams attribute success or failure to R&D is highlighted as an important factor. Top management teams with strong technology orientation teams exhibit unexpected patterns in decisions about R&D. This work deepens our understanding of the influence of performance feedback on decisions about R&D in technology-based firms.